A rectangular helix microwave structure for antenna applications - Kommalapati, Aneesh Chowdary (2014)
The project involves design, fabrication and testing of a novel broadband, circularly polarized, planar helix antenna operating at X-band that can be fabricated using printed circuit techniques. A circular helix antenna has been modified into a planar helix antenna, and the effect of various parameters like pitch angle, dimensions, feed and substrate, etc. on the impedance and radiation characteristics have been studied. The performance parameters under investigation have been S11, directivity, side lobe level, and axial ratio; these parameters have been obtained using CST Microwave Studio. The results of the simulation have been as follows; S11 was less than -10dB over a frequency of 8.3 – 11.7GHz, directivity ranged from 11.7 – 12.6dBi, side lobe level varied from -4.7dB to -16.1dB and finally axial ratio was between 0.68dB and 3.3dB. The final design has been fabricated using RO4003C dielectric substrates. The simulation results for the final design have been compared with measurement results. The measurement results for S-parameters match well with the simulation results thus leading to a circularly polarized antenna based on planar helix.